2022
DOI: 10.3390/agriculture12111903
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Community-Based Village Development Strategies in Indonesia: Using Multicriteria Decision Analysis

Abstract: To achieve a prosperous village community by utilizing all the potential and resources they have, village development needs to be carried out in a planned and sustainable manner by the village government and the community. This research aims to analyze alternative community-based village development strategies, and formulate the best strategies and programs for community-based village development. The data analysis method used is multicriteria decision analysis (MCDA). The location of this research is Parentas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In line with research conducted by Harrison & Schipani (2007), who said that to be able to alleviate poverty, the private sector also has an essential role in poverty alleviation. According to Nugraha et al (2022), the private sector and the community are not only placed as development objects but also must be played as executors from the planning stage to the implementation stage of a program. This collaboration can be carried out because the socio-cultural conditions in Indonesia are still closely related to the culture of gotong royong in carrying out life (Yuhertiana et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In line with research conducted by Harrison & Schipani (2007), who said that to be able to alleviate poverty, the private sector also has an essential role in poverty alleviation. According to Nugraha et al (2022), the private sector and the community are not only placed as development objects but also must be played as executors from the planning stage to the implementation stage of a program. This collaboration can be carried out because the socio-cultural conditions in Indonesia are still closely related to the culture of gotong royong in carrying out life (Yuhertiana et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nugraha et al, [17] Previous research suggested that it is better to first carry out an influence analysis of factors in community-based village development programs in determining alternative policy strategies.…”
Section: Publications Contributions Research Gapmentioning
confidence: 99%
“…This parallel positioning to rivers indicates that villages not only favor locations near water for practical reasons but also tend to expand along the rivers' flow, highlighting a strip pattern of growth and development. 1 Chinese Ethnic Minority Characteristic Villages; 2 List of Traditional Chinese Villages; 3 National Key Rural Tourism Villages; 4 Administrative Villages. Source: Prepared by the authors.…”
Section: Village Spatial Environmentmentioning
confidence: 99%
“…Scholarly research on traditional villages has evolved from initially focusing on describing and verifying the characteristics of these villages to encompassing a broader range of topics such as sustainability [4][5][6][7][8], conservation and development [9][10][11], residential environment [12,13], tourism development [14][15][16], and spatial morphology and distribution [17][18][19]. There is now a greater emphasis on studying the overall human habitat environment and the comprehensive value of traditional villages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation